Effect of breathing intervention in patients with COVID and healthcare workers - Rain, Manjari; Puri, Goverdhan Dutt; Bhalla, Aashish; Avti, Pramod; Subramaniam, Balachundhar; Kaushal, Vipin; Srivastava, Vinod; Mahajan, Pranay; Singh, Mini; Pandey, Navin; Malhotra, Pankaj; Goel, Sonu; et al. (Frontiers in Public Health, 2022)
Background: Regulated breathing facilitates ventilation and reduces breathlessness. However, the effect of Yogic breathing on COVID-patients remains unclear. We aimed to evaluate the efficacy of two breathing protocols i.e. Short breathing technique (SBT) and long duration breathing techniques (LBDT). Methods: Three groups including COVID-positive, COVID-recovered patients and health care workers (HCWs) were included in the study and segregated into Yoga and control groups. SBT was administered to COVID-positive patients. SBT and LBDT were administered to COVID-recovered and HCWs. Eighteen biochemical parameters, 6-minute walk test and 1-minute sit-stand test were assessed on 0, 7th and 15th day, where biochemical parameters were the primary outcome. Pre-post estimation of neuropsychological parameters (9 questionnaires) and heart rate variability was carried out. Paired t-test or Wilcoxon rank test was applied for pre-post comparison and Student t-test or Mann-Whitney U test was used for group comparison. Repeated measures test was applied for data recorded at 3-time points. Results: A significant elevation in WBC count was observed in COVID-positive intervention (p<0.001) and control groups (p=0.003), indicating no role of intervention on change in WBC number. WBC count (p=0.002) and D-dimer (p=0.002) significantly decreased in COVID-recovered intervention group. D-dimer was also reduced in HCWs practicing Yogic breathing as compared to controls (p=0.01). D-dimer was the primary outcome, which remained below 0.50 µg/ml (a cut-off to define severity) in CYG and decreased in RYG and HYG after intervention. Six-minute walk test showed an increase in distance covered among the COVID-positive (p=0.01) and HCWs (p=0.002) after intervention. The high-frequency power (p=0.01) was found reduced in the COVID-positive intervention group. No significant change in neuropsychological parameters was observed. Conclusion: Yogic breathing lowered D-dimer, which is helpful in reducing thrombosis and venous thromboembolism in COVID-19 patients besides lowering the chances of vaccine-induced thrombotic thrombocytopenia in vaccinated individuals. The breathing intervention improved exercise capacity in mild to moderate cases of COVID-19. Further studies can show if such breathing techniques can influence immunity-related genes, as reported recently in a study. We suggest that Yogic breathing may be considered an integrative approach for management of COVID-patients. Trial Registration: Clinical Trials Registry – India, CTRI/2020/10/028195 http://ctri.nic.in/Clinicaltrials/login.php